1983
DOI: 10.1073/pnas.80.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation and expression of murine mammary tumor proviruses in mouse thymoma cell lines.

Abstract: Murine mammary tumor virus (MMTV) expression is analyzed in a T-lymphoid cell line (TIMI) sensitive to the killing effect of glucocorticoids and in two of its variants, one resistant (TIMir) and one supersensitive (T MI"5) to glucocorticoidinduced lymphocytolysis. In the TIM, line, MMTV is expressed and induced approximately 10-fold by short treatment with dexamethasone. Southern blot analyses of restriction enzyme digests of DNA Glucocorticoids induce in a-variety of tissues specific responses by mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Even more relevant to the present results are the findings of Mermod et al [19] who found that the selection of a dexamethasone-resistant mouse lymphoid cell line (in the presence of 10#M dexamethasone) was specifically associated with demethylation of the 5'-long terminal repeats of MMTV in the absence of any MMTV genome rearrangements or overall genome demethylation.…”
Section: Discussionsupporting
confidence: 43%
“…Even more relevant to the present results are the findings of Mermod et al [19] who found that the selection of a dexamethasone-resistant mouse lymphoid cell line (in the presence of 10#M dexamethasone) was specifically associated with demethylation of the 5'-long terminal repeats of MMTV in the absence of any MMTV genome rearrangements or overall genome demethylation.…”
Section: Discussionsupporting
confidence: 43%
“…Since role in eukaryotic cell metabolism in general and in liver in particular (44), a gradual demethylation of the CpG b may take-place during development. A similar effect of glucocorticoids on the demethylation of mouse mammary tumor virus DNA has also been reported in some mutants of myeloma cells (45). Whether glucocorticoids and estradiol trigger the same mechanism of demethylation remains unknown.…”
Section: -Methylcytosine Tomentioning
confidence: 55%
“…No change in DNA methylation, however, could be detected during tyrosine aminotransferase induction by glucocorticoids in hepatoma cells, a short-term event (Lapeyre et al, 1980). Yet, experiments with MTV-infected lymphoid cells suggest that long-term treatment with glucocorticoids could lead to demethylation of the induced gene, and this might play a role in cell differentiation events induced by these hormones (Mermod et al, 1983). In any case, glucocorticoids induce the non-methylated transfected forms of MTV, but not their methylated endogenous forms (Groner et al, 1983b (Tymoczko et al, 1983;Rossini & Barbiroli, 1983).…”
Section: Transcriptional and Post-transcriptional Effectsmentioning
confidence: 98%